Conformal TCO-semiconductor-metal nanowire array for narrowband and polarization-insensitive hot-electron photodetection application - Zhang, Cheng (2018)
The use of hot electrons arising from the nonradiative decay of surface plasmons (SPs) is increasingly attracting interests in photodetection, photovoltaics, photocatalysis, and surface imaging. Nevertheless, the quantum efficiency of the hot-electron devices has to be improved to promote the practical applications. We propose an architecture of conformal TCO/semiconductor/metal nanowire (NW) array for hot-electron photodetection with a tunable optical response across the visible and near-infrared bands. The wavelength, strength, and bandwidth of the plasmonic resonance are tailored by controlling the lattice periodicity and topology. Finite-element simulation demonstrates that the near-perfect, polarization-insensitive, and ultranarrow-band optical absorption can be achieved in the conformal NW system. By the excitation of localized SPs, a strong field concentrates at the top corner of the NWs with a high hot-electrons generation rate. The analytical probability-based electrical calculation further shows that the SPs-enhanced photoresponsivity can be more than five times larger than that of the flat reference.